The Contribution Of Arm Length To The Skill Of Serving Under In Volleyball Game At Smk Negeri 5 Bengkulu Utara - Faruq, Al; Ertanto, Dodi; Asnawati, Asnawati (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the contribution between arm muscle strength to lower service skills in volleyball games at SMK Negeri 5 North Bengkulu. This type of research is correlational research. The research sample amounted to 20 people. The instruments used in this study were the pull up test and the lower serve test in volleyball games. Where the results of the contribution of arm muscle strength to the lower serve test amounted to 90.17%. With the discovery of a significant contribution of arm muscle strength to lower serve skills in volleyball games at SMK Negeri 5 Bengkulu Utara, arm muscle strength can be used as a tool to predict lower serve skills in volleyball games.